2002
DOI: 10.1021/bi015700a
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2 Directly Interacts with Aldolase via Its PH Domain

Abstract: Mammalian phospholipase D (PLD) has been implicated in the cellular signal transduction pathways leading to diverse physiological events and known to be regulated by many cellular factors. To identify the proteins that interact with PLD, we performed a protein overlay assay with fractions obtained from the sequential column chromatographic separation of rat brain cytosol using purified PLD2 as a probe. A protein of molecular mass 40 kDa, which was detected by anti-PLD antibody with overlaying of the purified P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 26 publications
1
57
0
1
Order By: Relevance
“…Molecular analysis of the interaction between endogenous Grb2 and PLD2 mutants revealed that (Xu et al, 2001), whereas residue Y 179 is conserved only in the PX domain of mammalian PLDs. The N-terminal region of PLD2, containing the PX (a.a. and domains, is the most representative region involved in PLD2 protein-protein interactions (Park et al, 2000;Kim et al, 2002;Ahn et al, 2003;Jang et al, 2003). The relevance of the PX domain is illustrated by the fact that its deletion from PLD2 produces a catalytically inactive enzyme in vitro (Sung et al, 1999;Park et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis of the interaction between endogenous Grb2 and PLD2 mutants revealed that (Xu et al, 2001), whereas residue Y 179 is conserved only in the PX domain of mammalian PLDs. The N-terminal region of PLD2, containing the PX (a.a. and domains, is the most representative region involved in PLD2 protein-protein interactions (Park et al, 2000;Kim et al, 2002;Ahn et al, 2003;Jang et al, 2003). The relevance of the PX domain is illustrated by the fact that its deletion from PLD2 produces a catalytically inactive enzyme in vitro (Sung et al, 1999;Park et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We examined the possibility of a protein-protein interaction between the PH domain and the CTD of ADL6 as a means by which the CTD could affect the lipid binding specificity of the PH domain. Recently it has been shown that the PH domain is also involved in protein-protein interactions (39,40). Interestingly, there was a strong interaction between the PH domain and the CTD at low salt concentrations.…”
Section: Fig 2 Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…For example, PLD2 activity may be modulated in vivo by inhibition (11). The reported inhibitors include a heat-stable 18-kDa protein (11), adolase (13), ceramide (14), ␣-actinin (15), and ␣-and ␤-synucleins (16). On the other hand, a lot of activators of PLD2 activity have also been found.…”
mentioning
confidence: 99%